Development of Flash Movie Learning Media with a SETS Vision to Improve Critical Thinking Skills and Learning Outcomes on Environmental Pollution Material - Ahmad Faisal Amri; Kartono Kartono (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to determine: the feasibility of flash movie learning media with a SETS vision for use in biology learning, the influence of flash movie learning media with a SETS vision on improving student’s critical thinking skills, and the influence of flash movie learning media with a SETS vision on improving student learning outcomes. The development procedure in this research refers to steps adapted from the Borg & Gall Model which include: collecting information, planning, developing an initial product form, conducting limited trials, carrying out revisions, conducting field trials, and carrying out revisions. The data analysis techniques used are descriptive statistics and inferential statistics using multivariate tests (MANOVA). The results of the research are as follows: The flash movie learning media has a SETS vision, from the media and material aspect it is in the "Very Good" category and has a significant influence on improving the critical thinking skills of class X F MAN Yogyakarta III students, this is proven by the MANOVA test which shows significance value (Sig.) = 6 x 10-9 with a confidence level of 95%. Flash movie learning media with the SETS vision has a significant influence on improving the learning outcomes of class X F MAN Yogyakarta III students, this is proven by the MANOVA test which shows a significance value (Sig.) = 0.001 with a confidence level of 95%.